Artificial finger joint replacement due to a giant cell tumor of the tendon sheath with bone destruction: A case report - LU, HUI (Oncol Lett, 2015)
The current study presents the case of a 25-year-old male who developed tumor recurrence of the proximal phalange of the ring finger on the right hand 4 years after partial tumor resection surgery. An X-ray of the right hand showed that the distal bone of the proximal phalange on the ring finger was destroyed. An artificial finger joint replacement was performed using a silicone joint for this unusual tumor recurrence. The pathological findings were indicative of a giant cell tumor of the tendon sheath. As a result of surgery, the patient's proximal interphalangeal point motion recovered to the pre-operative level. The pre-operative and post-operative disabilities of the arm, at shoulder and hand and total activity measurement values were 1.67 and 3.33, and 255 and 243°, respectively. Complications such as tumor recurrence, joint dislocation and the requirement for prosthetic training were not observed during the 5-year follow-up period.